2017
DOI: 10.1007/s13205-017-0700-2
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol production from non-detoxified and non-sterile lignocellulosic hydrolysate using low-cost industrial media components

Abstract: Immobilized Candida tropicalis cells in freeze dried calcium alginate beads were used for production of xylitol from lignocellulosic waste like corn cob hydrolysate without any detoxification and sterilization of media. Media components for xylitol fermentation were screened by statistical methods. Urea, KHPO and initial pH were identified as significant variables by Plackett-Burman (PB) design. Significant medium components were optimized by response surface methodology (RSM). Predicted xylitol yield by RSM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
11
0
3
Order By: Relevance
“…They found that medium components such as KH 2 PO 4 , yeast extract, (NH 4 ) 2 SO 4 and MgSO 4 ·7H 2 O had a significant effect on xylitol production. Likewise, Yewale et al performed Plackett–Burman (PB) design followed by CCD and reported components such as KH 2 PO 4 , yeast extract and xylose are the critical factors for xylitol production [ 36 ]. These studies indicate the importance of statistical method to identify the vital components affecting growth and product formation.…”
Section: Resultsmentioning
confidence: 99%
“…They found that medium components such as KH 2 PO 4 , yeast extract, (NH 4 ) 2 SO 4 and MgSO 4 ·7H 2 O had a significant effect on xylitol production. Likewise, Yewale et al performed Plackett–Burman (PB) design followed by CCD and reported components such as KH 2 PO 4 , yeast extract and xylose are the critical factors for xylitol production [ 36 ]. These studies indicate the importance of statistical method to identify the vital components affecting growth and product formation.…”
Section: Resultsmentioning
confidence: 99%
“…The yeast accumulated 3 2.0 g/L with conversion yield of 0.71 g/g from SCB while xylitol titer and yield achieved with rice straw were 12.5 g/L and 0.51 g/g, respectively. Similarly, de Freitas Branco et al [36]…”
Section: Optimization Of Media Components For Maximizing Xylitol Prodmentioning
confidence: 88%
“…3A & 3B). The xylose consumption was smooth as with pure xylose and a large fraction of initial xylose concentration of 20.0 g/L was consumed within 48 h. Both the strains exhibited high cell growth (OD 600 :[35][36][37][38] concomitant with xylose assimilation. The xylitol titer and yield obtained with mutant strain were 11.8 g/L and 0.59 g/g while wild type strain was able to accumulate 9.3 g/L xylitol with conversion yield of 0.46 g/g.…”
mentioning
confidence: 94%
“…5 A, D & E) and KH 2 PO 4 ( Fig. 5 B, [27] performed Plackett-Burman (PB) design followed by CCD and reported components such as KH 2 PO 4 , yeast extract and xylose are the key factors for xylitol production. These studies indicate the importance of statistical method to identify the important components affecting growth and product formation.…”
Section: Optimization Of Media Components For Maximizing Xylitol Prodmentioning
confidence: 99%